2019
DOI: 10.5860/llm.v33i4.7348
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in Academic Libraries

Abstract: The authors, who have each engaged in mentoring in higher education, surveyed academic librarians in 2017 on their mentoring experiences. Those findings are placed alongside best practices drawn from the literature to discover what motivates academic librarians to participate in mentoring and how it impacts them professionally and personally. Based on this evidence, the authors encourage colleagues to seek professional development through mentoring opportunities. “Sometimes our light goes out, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Mentoring is an investment in the LIS profession's future as staff members of the library are considered as the most precious assets. 34 So, why were there such varying degrees of mentoring practices in academic libraries in New England? Let's look at the mentoring definitions applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentoring is an investment in the LIS profession's future as staff members of the library are considered as the most precious assets. 34 So, why were there such varying degrees of mentoring practices in academic libraries in New England? Let's look at the mentoring definitions applied.…”
Section: Discussionmentioning
confidence: 99%
“…Burke and Tumbleson noted that "mentoring is profitable at any career stage." 7 Benefits included succession planning in Harrington and Marshall's study, 8 recruitment and retention, 9 and facilitating learning. 10 The James, Raynor, Bruno study on informal mentorship found value as it is more accessible to mentees than formal MPs, flexible without requiring structures, and most importantly, available in the library.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 2016 edition focused on more particular topics such as electronic resources, the librarian as content creator and copyright challenges. In their most recent survey, conducted in 2019, they reviewed the literature, methods and conclusions, encouraging librarians to evaluate their contributions and reassert their educational role (Burke and Tumbleson, 2019).…”
Section: Related Workmentioning
confidence: 99%